ENTREPRENEURIAL SPIRIT ON ENTREPRENEURIAL INTENTION OF INDONESIAN TRADITIONAL FOOD (CASE STUDY ON STUDENTS AND ALUMNI OF CIPUTRA UNIVERSITY TOURISM-CULINARY BUSINESS STUDY PROGRAM) - Gladys Rebecca; J. E. Sutanto; Michael Ricky Sondak (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of this study is to find out how the role of entrepreneurial spirit on entrepreneurial intention of Indonesian traditional food in students and alumni of Tourism-Culinary Busieness study program. The informants in this study are students, alumni, and an expert. This research uses qualitative methods. Data collection were carried out by initial survey, and followed by interviews to depeen the application of entrepreneurial spirit in traditional food business. Based on the results of the interview, it was concluded that entrepreneurial intention must go hand in hand with entrepreneurial spirit so that one's entrepreneurial activities can be run. The characters that must be contained in an entrepreneur include passion character in the form of passion of fighting in business, independent character in the form of the ability to position the business well, marketing character as sesnsitivity in the form of the ability to see and take opportunities by paying attention to customers, creative and innovative character as an effort to differentiate and add business value, calculated risk taker in the form of risky decision making by doing calculations, persistence in the form of perseverance and unyielding spirit when through obstacles, and high ethical standards in the form of ethics in doing business to build a good business image. But in reality the cultivation of characters and interests that should be, a little contrary to the character of today's students as millennials. Millennials have a tendency to want to be fast-paced, instant, and do not want to trouble themselves.